Keefektifan Galur PGPR dalam Pengendalian Penyakit Karat Putih dan Peningkatan Pertumbuhan Tanaman Krisan - WiyonoSuryo; SuryaningsihAndika Septiana; PratiwiAstika Widhi (Jurnal Fitopatologi Indonesia, 2023)
Effectiveness of Various PGPR Lineage in Controlling White Rust Diseases and Growth Promotion of Chrysanthemum White rust disease caused by Puccinia horiana is the most destructive disease of Chrysanthemum in Indonesia. There was no available effective control measure against the disease in Indonesia. This research aimed to examine the potency of five strains of plant growth-promoting rhizobacteria (PGPR) for controlling white rust disease on Chrysanthemum under field conditions. Five PGPR strains (Pseudomonas diminuta P14, Bacillus firmus J8, Lysinibacillus fusiformis C71, AKBR, AKS) and one commercially formulated PGPR were used in this study. The research was carried out in farmer fields with a randomized complete block experimental design. PGPR was applied by plant watering using bacterial suspension. All PGPR strains were effective in suppressing the white rust disease incidence and its severity. The most effective PGPR strain to suppress white rust disease was Bacillus firmus J8 and the most effective strain to increase the growth of Chrysanthemum plants was Lysinibacillus fusiformis C71. The five PGPR strains tested and commercial formulation increased the diameter of the flower.